Synthesis, Characterization, DNA Cleavage, Antimicrobial and Catalytic Studies of Tridentate (N3) Schiff Base Ligand and its Complexes with Transition Metal Ions - Gandhi, S. Rajiv; Kumar, D. Sathis; Srinivasan, R.; Sheriff, A.K. Ibrahim (Asian Journal of Chemistry, 2016)
Transition metal complexes of Mn(II), Fe(III), Co(II), Ni(II) and Cu(II) ions have been synthesized from cinnamaldehyde and diethylene-triamine. The complexes have been characterized by elemental analysis, molar conductance, magnetic susceptibility, FT-IR, electronic spectra, 1H NMR, 13C NMR, ESR, mass spectra and thermal studies. Their ligand field parameters have also been calculated. Hydrolysis of ethyl acetate has been studied by using the complexes as homogeneous catalysts. The DNA cleavage activities of Schiff base and its metal complexes have been monitored by agarose gel electrophoresis method in the presence of hydrogen peroxide. The antimicrobial activities of ligand and its metal complexes have been examined on the fungi Candida albicans and Aspergillus niger and bacteria Staphylococcus aureus, Escherichia coli and Bacillus cereus.